(untitled) (Gestionar: revista de empresa y gobierno, 2022)
The objective was to propose tourism development strategies based on the dimensions of culture, which allow the strengthening of the Virgen de la Candelaria Festival of Puno in Peru. The deductive, descriptive and correlational method was used. The tourist services satisfaction index is high at 4.23/5, tourist spending is more than 300, attractive for investment and expansion of the tourist plant. The Pearson correlation is 0.64 between the study variables, 0.79% contribution to the GDP of the Festival in three days, which generates 10.7% of local employment, spending on culture is 106 times the national average, social participation of 99.22%, the importance as world heritage of 4.14/5 and 69.8% of fiction content on television are acceptable, thus being the dimensions of economy, social participation and communication as the most influential. The strengthening of the management of the Festival should be focused on quality, training, institutional strengthening, planning and ordering of space and promotion.